Ancaman dan Strategi: Krisis Kesehatan Mental pada Anak Komunitas K-Pop selama Pandemi COVID-19 - Hafida Jauhari Rahmah; Mustaqim Pabbajah; Ratri Nurina Widyanti (UIN Fatmawati Sukarno Bengkulu, Indonesia, 2022)
Mental health is a crucial issue discussed during the COVID-19 pandemic. This study is based on the pandemic situation that took place in the last two years which resulted in the youth mental health crisis in Indonesia. This study aims to explain adolescent mental health disorders during a pandemic, as experienced by the K-Pop community in Yogyakarta. This research was conducted on subjects in the Yogyakarta area such as Bantul Regency, Sleman Regency and Yogyakarta City with subjects consisting of 9 teenagers from the K-Pop community. The research data were collected using interviews and documentation. The results of this study indicate that there have been a number of mental disorders experienced by adolescents such as symptoms of stress, anxiety and depression. Mental disorders that occur due to economic factors, physical factors and social restrictions and interaction factors. K-Pop teenagers are able to overcome mental disorders during the pandemic through a number of activities, including; independent meditation, physical and medical activity. This study suggests the need for careful attention to mental health threats among adolescents so as not to cause ongoing trauma.